Epoxy resin composition and application thereof
By using a modified nuclear shell rubber enhanced epoxy resin composition, the problem of fracture toughness and insufficient anti -fatigue resistance of wind power blades under the force of shear effects, realized the situation that does not reduce the amount of Yang's modular and impact strength. Below, significantly improve the effect of fracture toughness.
Patent Information
- Application Number
- CN202411347025.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The prior art is difficult to improve the fracture toughness and fatigue resistance of wind power blades without sacrificing Young's modulus and impact strength, especially when subjected to vertical and parallel shear forces.
Provides an epoxy resin composition, which contains epoxy resin, polyetheride curing agent and modified core shell rubber. The modified riblon rubber is formed by the core and methanes and cross -linked acrylics formed by the silicide monomer and the cross -linked agent. The shell composition of acrylate and connects the surface covering agent through a chemical key.
The epoxy resin composition significantly improves the fracture toughness and fatigue resistance of wind power blades without sacrificing Yang's modular and impact intensity, especially under the force of cutting.
Smart Images

Figure CN118852850B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to an epoxy resin composition and its application. Background Art
[0002] As the world strives to address climate change, renewable energy has become the core of future energy development. Wind energy is a clean renewable energy source, and the wind power industry is one of the most important application areas for composite materials in the world. Wind turbine blades are an important part of wind turbines, and their quality and performance directly affect the operating efficiency and safety of wind turbines. However, since wind turbines have been working in places with harsh climatic conditions for a long time, they are subjected to impact, fatigue and environmental loads during operation, resulting in cracks, corrosion holes, cracks and other defects in the blades.
[0003] Glass fiber reinforced polymer composites (GFRP) are one of the most popular materials for manufacturing wind turbine blades, with advantages such as high strength, high stiffness, and insensitivity to fatigue. Generally, there are significant differences in the mechanical properties of GFRP structures in different directions. They have higher strength and stiffness along the fiber direction, but insufficient strength in the thickness direction (perpendicular to the fiber direction). Therefore, when subjected to shear force impact loads in the transverse or thickness direction, interlaminar cracks are easily generated, resulting in interlaminar delamination failure of GFRP. This failure phenomenon will reduce the overall performance of the composite material to varying degrees.
[0004] There are various methods to improve the interlaminar fracture toughness of GFRP, including interlaminar toughening, matrix toughening and nanomaterial modification toughening. Among them, matrix toughening has been widely studied because a high-toughness matrix can absorb more energy during crack propagation, thereby inhibiting the rapid propagation of cracks. The most common method for resin matrix toughening is to add rubber particles, thermoplastic fillers or rigid fillers to the matrix resin. Core-shell rubber particles (CSP) with a soft core-hard shell structure can significantly improve the toughness of the matrix resin while maintaining thermal properties to a certain extent. However, at present, there is insufficient research on the combination of CSP and glass fiber, that is, how to show better fracture toughness without sacrificing Young's modulus and impact strength, and how to improve the excellent fracture toughness and fatigue resistance of wind turbine blades when subjected to shear forces perpendicular to and parallel to the wind turbine blades is an urgent problem to be solved. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an epoxy resin composition that can be used in wind turbine blades to improve the fracture toughness of the wind turbine blades.
[0006] In a first aspect, the present application provides an epoxy resin composition, characterized in that the epoxy resin composition comprises component A, component B and component C, the mass ratio of component A to component C is 60-95:5-40, and the mass ratio of the total mass of component A and component C to component B is 100:18-35;
[0007] Wherein, component A is epoxy resin;
[0008] Component B is a polyetheramine curing agent;
[0009] Component C is a modified core-shell rubber, which includes a core formed by a first polymer and a shell formed by a second polymer, wherein the first polymer is a polysiloxane formed by a siloxane monomer and a crosslinking agent methyltriethoxysilane, and the second polymer is a polymer of a methacrylate monomer or an acrylate monomer, and a surface coating agent is connected to the shell formed by the second polymer through a chemical bond, and the surface coating agent is KH570 or glycidyl methacrylate, and the mass ratio of the siloxane monomer, the crosslinking agent, the methacrylate monomer or the acrylate monomer, and the surface coating agent is 25-35:4-8:20-25:1-5; the average particle size of the modified core-shell rubber is less than 300nm, and the average particle size of the core is less than 200nm.
[0010] Preferably, the mass ratio of the siloxane monomer, the crosslinking agent, the methacrylate monomer or the acrylate monomer, and the surface coating agent is 28-32:4-6:21-23:2-4; for example, the mass ratio is 30:5:22.1:3.7 or 30:5:22.1:2.1.
[0011] Preferably, the average particle size of the modified core-shell rubber is 300 nm or less, preferably 200 nm or less, and further preferably 100 nm or less, for example 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm; the particle size D90 of the modified core-shell rubber is 300 nm or less, preferably 200 nm or less, and further preferably 100 nm or less, for example 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm.
[0012] Preferably, the average particle size of the core of the modified core-shell rubber is 200 nm or less, preferably 100 nm or less, more preferably 60 nm or less, for example 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm; the D90 of the core of the modified core-shell rubber is 200 nm or less, preferably 100 nm or less, more preferably 60 nm or less, for example 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm, 61 nm, 62 nm, 63 nm, 64 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm. nm, 85 nm, 90 nm, 95 nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm.
[0013] Preferably, the siloxane monomer is one, two or more of octamethylcyclotetrasiloxane, hexamethylcyclotrisiloxane and decamethylcyclopentasiloxane; the methacrylate monomer is selected from methyl methacrylate, ethyl methacrylate or propyl methacrylate, and the acrylate monomer is selected from methyl acrylate, ethyl acrylate or propyl acrylate.
[0014] Preferably, the epoxy resin is a mixture of bisphenol A epoxy resin and polyurethane modified epoxy resin, and the mass ratio of the bisphenol A epoxy resin to the polyurethane modified epoxy resin is 4-20:1, for example, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1.
[0015] Preferably, the mass ratio of component A to component C is 60-95:5-40, for example 95:5, 90:10, 85:15, 80:20, 70:30, 60:40.
[0016] Preferably, the mass ratio of the total mass of component A and component C to component B is 100:18-30, for example 100:18, 100:19, 100:20, 100:21, 100:22, 100:23, 100:24, 100:25, 100:26, 100:27, 100:28, 100:29, 100:30.
[0017] Preferably, the modified core-shell rubber is prepared by an emulsion polymerization method, comprising the following steps:
[0018] S1: mixing and emulsifying a siloxane monomer, a crosslinking agent, a surfactant, an acidic catalyst, an emulsifier and water, adjusting the pH to neutral after the reaction is completed, adding a free radical initiator and stirring for 20-60 minutes to obtain an emulsion A, wherein the crosslinking agent is selected from methyltriethoxysilane;
[0019] S2: adding methacrylate or acrylate to the emulsion A obtained in step S1, mixing and emulsifying to obtain emulsion B;
[0020] S3: adding a surface coating agent to the emulsion B, reacting for a period of time, and then adding a terminator to terminate the reaction, wherein the surface coating agent is KH570 or glycidyl methacrylate.
[0021] Preferably, the acidic catalyst is selected from p-toluenesulfonic acid and dodecylbenzenesulfonic acid;
[0022] Preferably, the emulsifier is selected from OP-10;
[0023] Preferably, the surfactant is selected from sodium lauryl sulfate, sodium oleoyloxyethanesulfonate, or sodium fatty alcohol polyoxyethylene ether sulfate;
[0024] Preferably, the free radical initiator is selected from potassium persulfate;
[0025] Preferably, the terminator is selected from p-methoxyphenol or hydroquinone;
[0026] Preferably, the mass ratio of the siloxane monomer, the crosslinking agent, the acidic catalyst, the emulsifier, the surfactant, the methacrylate or acrylate, and the surface coating agent is 25-35:4-8:0.5-2:0.5-2:0.5-2:20-25:1-5, and more preferably, the mass ratio is 28-32:4-6:1-2:1-2:1-2:21-23:2-4; for example, the mass ratio is 30:5:1:1:1:22.1:3.7 or 30:5:1:1:1:22.1:2.1; the mass volume ratio of the siloxane monomer and water is 1g:(8-12)mL;
[0027] Preferably, the reaction temperature of step S1 is 60-100° C., and the reaction time is 2-5 hours, for example, the reaction temperature is 80° C., and the reaction time is 3 hours;
[0028] Preferably, the reaction temperature of step S2 is 60-100° C., and the reaction time is 2-5 hours, for example, the reaction temperature is 80° C., and the reaction time is 3 hours;
[0029] Preferably, the reaction temperature of step S3 is 60-100° C., and the reaction time is 0.5-2 hours, for example, the reaction temperature is 80° C., and the reaction time is 1 hour.
[0030] Preferably, steps S1-S3 are performed under nitrogen protection.
[0031] Preferably, the method further comprises step S4: demulsifying and freeze-drying the product obtained in step S3; further preferably, step S4 is to add a CaCl2 solution to the product obtained in step S3 for demulsification treatment, and then freeze-dry at a temperature below -30°C; for example, the freeze-drying temperature can be selected from -30°C, -40°C, -50°C, and -60°C.
[0032] Preferably, the modified core-shell rubber is modified core-shell rubber particles having an average particle size of 300 nm or less and an average particle size of the core of 200 nm or less.
[0033] Preferably, the modified core-shell rubber particles are obtained by demulsification and freeze-drying.
[0034] Preferably, the modified core-shell rubber particles are prepared by demulsification treatment with a CaCl2 solution and then freeze-drying at a temperature below -30°C to remove moisture; preferably, the freeze-drying temperature can be selected from -30°C, -40°C, -50°C, and -60°C.
[0035] Preferably, the average particle size of the modified core-shell rubber particles is 300 nm or less, preferably 200 nm or less, and further preferably 100 nm or less, for example 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm; the particle size D90 of the modified core-shell rubber particles is 300 nm or less, preferably 200 nm or less, and further preferably 100 nm or less, for example 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300nm.
[0036] Preferably, the average particle size of the core of the modified core-shell rubber particles is 200 nm or less, preferably 100 nm or less, more preferably 60 nm or less, for example 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm; the D90 of the core of the modified core-shell rubber particles is 200 nm or less, preferably 100 nm or less, more preferably 60 nm or less, for example 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm, 61 nm, 62 nm, 63 nm, 64 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm. nm, 85 nm, 90 nm, 95 nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm.
[0037] In a second aspect, the present application provides a prepreg comprising the epoxy resin composition as described above and glass fiber.
[0038] In a third aspect, the present application provides a fiber-reinforced composite material, which is obtained by curing the prepreg as described above.
[0039] In a fourth aspect, the present application provides a method for preparing a fiber-reinforced composite material, the method comprising curing the prepreg as described above.
[0040] Preferably, the curing temperature is 50-150°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C.
[0041] Preferably, the curing time is 4-10 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours.
[0042] The method further comprises preparing the fiber reinforced composite material by vacuum assisted resin injection (VARI) process using the epoxy resin composition as described above. Preferably, the whole injection process is carried out under vacuum and room temperature conditions.
[0043] In a fifth aspect, the present application provides the use of the epoxy resin composition, prepreg, and fiber-reinforced composite material as described above in a wind turbine blade, wherein the epoxy resin composition, prepreg or fiber-reinforced composite material can improve the fracture toughness of the wind turbine blade.
[0044] Beneficial Effects
[0045] The epoxy resin composition of the present application exhibits excellent bending properties, tensile shear properties, type I double cantilever beam (DCB) performance and type II end notch bending (ENF), and water flow impact test, and exhibits a more excellent toughening effect without sacrificing Young's modulus and impact strength, thereby improving the fracture toughness of wind turbine blades and realizing its application in wind turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 TEM image of KH570 coated core-shell rubber particles KCSP of Example 1;
[0047] Figure 2 TEM image of the GMA-coated core-shell rubber particles GCSP of Example 2;
[0048] Figure 3 FTIR images of the core-shell rubber particles prepared in Examples 1 and 2;
[0049] Figure 4 The DCB diagram of the toughened GFRP laminate of the control group;
[0050] Figure 5 DCB diagram of GFRP laminate toughened with epoxy resin mixture 5-K. DETAILED DESCRIPTION
[0051] The technical solution of the present application will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present application and should not be construed as limiting the scope of protection of the present application. All technologies implemented based on the above content of the present application are included in the scope that the present application is intended to protect.
[0052] The present application is further described below through specific embodiments.
[0053] raw material:
[0054] Methyl methacrylate (MMA) and glycidyl methacrylate (GMA), KH570 silane coupling agent, octamethylcyclotetrasiloxane (D4), methyltriethoxysilane (MTES), sodium dodecyl sulfate (SDS), emulsifier OP-10, p-toluenesulfonic acid (PTSA), potassium persulfate (KPS), p-methoxyphenol (MEHQ), sodium bicarbonate (NaHCO3) and calcium chloride (CaCl2) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. and were not treated before use.
[0055] Vacuum infusion epoxy resin: 10 parts of polyurethane modified epoxy resin NPER-133, with an epoxy value of 0.41-0.51 [eq / 100g], and 90 parts of bisphenol A epoxy resin NPEL-128, both purchased from Nanya Electronic Materials (Kunshan) Co., Ltd., were mixed in a ratio of 10:90, and have the characteristics of low mixed viscosity and good wettability to glass fiber and carbon fiber.
[0056] Polyetheramine: Model GE-7124B, purchased from Huibai New Materials Technology (Shanghai) Co., Ltd., amine value of 470-570 [mgKOH / g], mixing ratio of 100:30 by weight.
[0057] Glass fiber cloth: purchased from Cangzhou Tuochuanao Building Materials Co., Ltd., with a surface density of 450 g / m 2 .
[0058] Example 1: Preparation of KH570 coated core-shell rubber and its particles
[0059] Octamethylcyclotetrasiloxane (30 g), MTES (5 g), SDS (1.0 g) and OP-10 (1.0 g) were dispersed in 300 mL of distilled water and stirred at 12,000 rad / min for 10 minutes. After stirring, the obtained mixture and the acid catalyst PTSA (1 g) were added to a three-necked flask equipped with a mechanical stirrer, a reflux condenser and a thermometer, and placed in an 80 °C oil bath for stirring and reaction for 3 hours. After the reaction was completed, the emulsion was neutralized to neutrality using sodium bicarbonate. After adding 0.3 g of free radical initiator KPS, the mixture was stirred for 30 minutes. MMA (22.1 g) was added to the flask at a drip rate of 10 mL / h and stirred continuously at 80 °C for 3 hours. Subsequently, KH570 (3.7 g) was added to the emulsion at a rate of 10 mL / h, the mixture was stirred and reacted for 1 hour, and finally 0.1 g MEHQ was added to terminate the reaction to obtain KH570-coated core-shell rubber emulsion. All the above reactions were carried out under nitrogen protection.
[0060] CaCl2 solution was added to the KH570 coated core-shell rubber latex for demulsification treatment, and then freeze-dried at -50°C to remove moisture to obtain solid powder particles KCSP.
[0061] Example 2: Preparation of GMA-coated core-shell rubber and its particles
[0062] The same procedure was followed as in Example 1, except that KH570 (3.7 g) was replaced with GMA (2.1 g).
[0063] A CaCl2 solution was added to the GMA-coated core-shell rubber latex for demulsification treatment, and then freeze-dried at -50°C to remove moisture to obtain solid powder particles GCSP.
[0064] Example 3: Preparation of epoxy resin mixture with KH570 coated core-shell rubber particles
[0065] 5.3 g, 11.2 g, 15.9 g, 21.2 g, 31.8 g, and 42.4 g of the solid powder particles KCSP prepared in Example 1 were respectively blended with 100 g of vacuum infusion epoxy resin to obtain epoxy resin mixtures in which the addition amount of solid powder particles accounted for 5 wt%, 10 wt%, 15 wt%, 20 wt%, 30 wt%, and 40 wt% of the total mass of the particles and the epoxy resin, and were respectively recorded as 5-K, 10-K, 15-K, 20-K, 30-K, and 40-K.
[0066] Example 4: Preparation of an epoxy resin mixture with GMA-coated core-shell rubber particles 5.3 g, 11.2 g, 15.9 g, 21.2 g, 31.8 g, and 42.4 g of the solid powder particles GCSP prepared in Example 2 were blended with 100 g of vacuum infusion epoxy resin, respectively, to obtain epoxy resin mixtures in which the addition amount of solid powder particles accounted for 5 wt%, 10 wt%, 15 wt%, 20 wt%, 30 wt%, and 40 wt% of the total mass of the particles and the epoxy resin, and were recorded as 5-G, 10-G, 15-G, 20-G, 30-G, and 40-G, respectively.
[0067] Example 5: Preparation of GFRP laminate toughened by modified core-shell rubber particles
[0068] Arrange 8 layers of glass fiber cloth in a staggered manner of [90 / 0] to obtain a laminate with a central [0 / 0] ply interface, and insert a 20um thick polytetrafluoroethylene release film in the center to form a 60 mm long crack. The epoxy resin mixtures 5-K, 10-K, 15-K, 20-K, 30-K, 40-K and 5-G, 10-G, 15-G, 20-G, 30-G, 40-G obtained in Example 3 and Example 4 were respectively prepared with curing agent polyetheramine, and a composite laminate was prepared by vacuum assisted resin injection (VARI) process. Full vacuum and room temperature conditions were used throughout the entire process of introduction. After the introduction was completed, the laminate was cured at 50°C for 4 hours and then at 70°C for 7 hours. The epoxy resin mixture and the curing agent polyetheramine were prepared according to the following mass ratio:
[0069]
[0070] Example 6: Preparation of Control Group Epoxy GFRP Laminates
[0071] Refer to Example 5, except that the epoxy resin mixture obtained in Example 3 or Example 4 is replaced with pure epoxy resin (without adding modified core-shell rubber particles), and the ratio of pure epoxy resin to curing agent polyetheramine is 10:3.
[0072] Comparative Example 1:
[0073] KH570-coated polymer core-shell particles were prepared by referring to Example 1, except that octamethylcyclotetrasiloxane (D4) (30 g) and MTES (5 g) were replaced with butyl acrylate (35 g). Other conditions were the same as those in Example 1, and KH570-coated polymer core-shell particles (BCSP) with a core of polybutyl acrylate (PBA) and a shell of polymethyl (meth)acrylate (PMMA) were prepared.
[0074] 15.9 g of the KH570 coated polymer core-shell particles (BCSP) prepared above was blended with 100 g of vacuum infusion epoxy resin to obtain an epoxy resin mixture in which the amount of polymer core-shell particles added accounted for 15 wt% of the total mass of the particles and the epoxy resin, which was recorded as 15-B.
[0075] A GFRP laminate toughened by KH570-coated polymer core-shell particles BCSP was prepared according to the method of Example 5, except that the epoxy resin mixture 15-K or 15-G obtained in Example 3 and Example 4 was replaced by 15-B.
[0076] Comparative Example 2: Refer to Comparative Example 1, except that KH570 (3.7 g) was replaced by GMA (2.1 g).
[0077] Comparative Example 3: The same method as in Example 2 was used, except that MMA (22.1 g) and GMA (2.1 g) were added to the flask at the same time for reaction, and the reaction was stirred continuously at 80 °C for 4 h before adding 0.1 g MEHQ to terminate the reaction.
[0078] Testing and Experimentation:
[0079] 1. Morphological characterization of modified core-shell rubber particles
[0080] (1) The morphology and size of the modified core-shell rubber particles were observed by transmission electron microscopy (TEM, FEI Tecnai 20, USA). The TEM results of KH570-coated core-shell rubber particles and GMA-coated core-shell rubber particles are shown in Figure 2. Figure 1 , 2 shown.
[0081] Due to the difference in composition between the core and shell of the rubber particles, it can be clearly observed Figure 1 , 2 In the figure, the darker part is the core polymer, and the relatively lighter part wrapped around it is the shell polymer.
[0082] (2) The particle size and distribution of modified core-shell rubber particles were measured by laser light scattering nanoparticle size and potential analyzer. The experimental results show that the particle size distribution of KH570-coated core-shell rubber particles and GMA-coated core-shell rubber particles is narrow and monodisperse. The average particle size of KH570-coated core-shell rubber particles is 84.53nm, D90 is 87.54nm, of which the average particle size of the core is 56.82nm, D90 is 62.27nm; the average particle size of GMA-coated core-shell rubber particles is 84.78nm, D90 is 90.49nm, of which the average particle size of the core is 52.08nm, D90 is 63.83nm.
[0083] (3) Fourier transform infrared spectrometer (FTIR, Thermo Nicolet 5700, USA) was used to analyze the chemical structure of the modified core-shell rubber particles. Figure 3 As shown in the figure, it can be seen that the infrared curve of GMA-coated core-shell rubber particles GCSP is at 910 cm -1 There is a characteristic peak of epoxy group at 1130cm -1 1113cm -1 The peak here is the silicon-oxygen peak, and the peak intensity increases, indicating that the KH570 coating is successful.
[0084] 2. Curing behavior of epoxy resin mixture
[0085] The curing reaction exothermicity of the epoxy resin mixture was analyzed by differential scanning calorimetry (DSC, Q20, NETZSCH). Nitrogen was used as the protective gas and purge gas, and the heating rate was 10 ℃ / min.
[0086] The curing conditions of epoxy resin mixtures 5-K, 10-K, 15-K, 20-K, 30-K, 40-K, 5-G, 10-G, 15-G, 20-G, 30-G, 40-G and the control group were tested by DSC. The addition of modified core-shell rubber particles with different compositions and structures had almost no effect on the starting temperature, peak temperature and termination temperature of the curing reaction. This is because there are no active groups on the surface of these modified core-shell rubber particles to participate in or interfere with the reaction between epoxy resin and curing agent. Therefore, these epoxy resin mixtures can be cured in the same way as pure epoxy resin in practical applications.
[0087] 3. Mechanical properties of GFRP laminates
[0088] The following tests were conducted on epoxy resin mixtures 5-K, 10-K, 15-K, 20-K, 30-K, 40-K and 5-G, 10-G, 15-G, 20-G, 30-G, 40-G and the control group and comparative examples 1-3 toughened GFRP laminates.
[0089] (1) Tensile, bending and fracture toughness tests
[0090] The mechanical properties of the samples, including tension, bending and fracture toughness, were tested by a universal mechanical testing machine (AGX-100 plus, Shimadzu, Japan). The tensile and bending tests were carried out according to ASTM D638 and ASTM D790, respectively. The fracture toughness of the samples was studied by a three-point bending test. The impact test of the composites was carried out at room temperature by a pendulum impact tester (CEAST 9050, Instron, Italy) according to ASTM D256.
[0091] The values reported in each group of the above mechanical property tests are the average values of five valid specimens.
[0092] The results of the tensile, bending and impact tests are summarized in Table 1, and the average values are recorded.
[0093] Table 1 Tensile, flexural and impact properties of GFRP laminates with different addition ratios of modified core-shell rubber particles
[0094]
[0095] The tensile stress-strain curve, tensile strength and tensile modulus, flexural stress-strain curve, flexural strength and flexural modulus, impact strength and impact fracture energy of GFRP laminates with different modified core-shell rubber particle addition ratios are improved compared with the control group, especially 15G and 20K. It can be seen that the GFRP laminates toughened by KH570 and GMA coated core-shell rubber particles can improve the tensile strength and flexural strength without sacrificing Young's modulus.
[0096] (2) Lap tensile shear test
[0097] Tensile shear tests were carried out using a universal mechanical testing machine (AGX-100 plus, Shimadzu, Japan) in accordance with GB / T33334—2016 standard.
[0098] Tensile shear strength Calculated by the following formula:
[0099]
[0100] In the formula is the tensile shear strength (MPa), F m is the maximum load (N), B is the width of the overlap area (mm), and L is the length of the overlap area (mm).
[0101] The glass fiber laminate in this test is model 3240 epoxy glass fiber board purchased from Shenzhen Quanfu Metal Co., Ltd.
[0102] The overlap tensile shear test is to add a pad at the end of the substrate to form a geometrically antisymmetric structure specimen. Under the action of an axial tensile load parallel to the overlap surface, the specimen is destroyed and the shear stress at the overlap is measured. The values of the tensile shear strength τ are shown in Table 2. It can be seen that the addition of different modified core-shell rubber particles improves the tensile shear strength of the GFRP laminate, especially 15G and 20K.
[0103] (3) End notch bending (ENF) test
[0104] The type II end notch bending (ENF) test was conducted using a universal mechanical testing machine (AGX-100 plus, Shimadzu, Japan) according to the JC / T773-2010 / ISO14130:1997 standard. The ENF specimens were tested using a three-point bending fixture, and the loading speed was also 1 mm / min. The interlaminar shear strength was calculated using the following formula:
[0105]
[0106] Where G ⅡC is the interlaminar shear strength (MPa), F is the maximum load (N), b is the specimen width (mm), and h is the specimen thickness (mm).
[0107] The mode II interlaminar fracture toughness of GFRP laminates was tested under three-point bending load by end notch bending (ENF) test. ⅡC The data are summarized in Table 2.
[0108] Table 2 Tensile shear strength τ and interlaminar shear strength G of GFRP laminates with different addition ratios of modified core-shell rubber particles ⅡC
[0109]
[0110] Compared with the control group, the addition of different modified core-shell rubber particles has an impact on the G ⅡC All of them have been improved to a certain extent. The G of GFRP laminates with 15-G, 15-K, 20-G and 20-K ⅡC The improvement is significant, while in the comparative example GⅡC And was not promoted.
[0111] (4) Double cantilever beam (DCB) test
[0112] Test method: A type I double cantilever beam (DCB) test was performed using a universal mechanical testing machine (AGX-100 plus, Shimadzu, Japan) according to GB / T28891-2012 / ISO standard. The laminate was cut into 120mm×20mm specimens, and a 60mm long polytetrafluoroethylene release film was embedded in the front end. The front 15mm of the release film was sanded, and the piano hinge was fixed to the top and bottom of the specimen by epoxy AB glue. The specimen was initially loaded to unload the load 3-5mm behind the release film, and then loaded again to 50mm behind the release film. The side of each specimen was marked with a black calibration scale to better observe the crack propagation, and the load-displacement value was recorded every 5mm until it extended to 50mm behind the release film. During the test, the load was applied perpendicular to the crack plane at a loading speed of 4 mm / min.
[0113] The test data are shown in Table 3, which includes four interlaminar fracture toughness values. The first is the initial fracture energy (GIC, init) at which the load and displacement curves begin to deviate from the straight line during the initial loading process. The second is the crack propagation energy (GIC, prop) at which the load and displacement begin to deviate from the straight line during the second loading process. The third is the initial critical energy release rate (VIS, init) from the edge of the specimen to the starting point of delamination during the initial loading process. The fourth is the initial critical energy release rate (VIS, prop) from the edge of the specimen to the starting point of delamination during the second loading process.
[0114] Table 3 Type I interlaminar toughness of GFRP laminates with different addition ratios of modified core-shell rubber particles
[0115]
[0116] As can be seen from Table 3, the fracture toughness values of the GFRP laminates with different modified core-shell rubber particles added are higher than those of the control group and the comparative example.
[0117] The DCB diagrams of the control group and 5-K toughened GFRP laminates are shown in Figure 4 , 5 As shown, SCF bridging phenomenon can be observed in the crack propagation region ( Figure 5 ), and the SCF bridging effect occurs from the initial stage until the end of crack propagation.
[0118] (5) High-pressure water impact test
[0119] The GFRP laminates were subjected to high-pressure water flow impact using a programmable rain test machine (HT-IP9K-1000L, Huitai).
[0120] The GFRP laminate was subjected to 0°C angle impact at a water pressure of 8~10Mpa using a programmable rain tester, the temperature was set at 35°C, and the plate was taken out for mass weighing after 5 hours. The mass changes are summarized in Table 4. It can be seen that after 5 hours, the mass retention rate of adding different modified core-shell rubber particles is higher than that of the control group and the comparative example, and the mass retention rate is more than 95.54%. This shows that the GFRP laminate with the modified core-shell rubber particles added has better resistance to high-pressure water flow impact.
[0121] Table 4 Weight of GFRP laminates with different addition ratios of modified core-shell rubber particles after high-pressure water flow impact
[0122]
[0123] The above tests show that the core prepared by the siloxane monomer and the crosslinking agent in the present application, after the shell layer is polymerized and the shell layer surface is coated with the coating agent, the obtained core-shell particles have excellent particle size and morphology, and can improve toughness and thus be suitable for use in wind turbine blades. However, the core-shell particles prepared by using butyl acrylate as the core in Comparative Examples 1 and 2 cannot be used in GFRP laminates in the present application, and their mechanical properties are poor, which greatly reduces the impact strength and cannot be used in outdoor wind turbine blades in harsh environments.
[0124] On the other hand, the shell-coated modified core-shell particle preparation method provided in the present application is superior to the conventional shell one-pot copolymerization method. The step-by-step modified preparation method makes the competitive reaction activity of particle growth uniform. The homogenized reaction of activity greatly reduces the unevenness, agglomeration, shell breakage, and different structures of core-shell particles caused by the difference in the reaction activity of the substances, thereby solving the problems of poor uniformity and poor performance of the modified core-shell toughening agent in the resin composition. In addition, the KCSP core-shell particles focus on contributing G ⅠC The interlaminar fracture toughness of GCSP core-shell particles is more focused on G ⅡC Improvement of interlaminar fracture toughness.
[0125] The above is a description of the exemplary implementation of the present application. However, the protection scope of the present application is not limited to the above implementation. Any modification, equivalent replacement, improvement, etc. made by those skilled in the art within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An epoxy resin composition, characterized in that The epoxy resin composition comprises component A, component B and component C, the mass ratio of component A to component C is 60-95:5-40, and the mass ratio of the total mass of component A and component C to component B is 100:18-35; Wherein, component A is epoxy resin; Component B is a polyetheramine curing agent; Component C is a modified core-shell rubber, which includes a core formed by a first polymer and a shell formed by a second polymer, wherein the first polymer is a polysiloxane formed by a siloxane monomer and a crosslinking agent methyltriethoxysilane, and the second polymer is a polymer of a methacrylate monomer or an acrylate monomer, and a surface coating agent is chemically bonded to the shell formed by the second polymer, wherein the surface coating agent is KH570 or glycidyl methacrylate, and the mass ratio of the siloxane monomer, the crosslinking agent, the methacrylate monomer or the acrylate monomer, and the surface coating agent is 25-35:4-8:20-25:1-5; the average particle size of the modified core-shell rubber is less than 300 nm, and the average particle size of the core is less than 200 nm; The modified core-shell rubber is prepared by an emulsion polymerization method, comprising the following steps: S1: mixing and emulsifying a siloxane monomer, a crosslinking agent, a surfactant, an acidic catalyst, an emulsifier and water, adjusting the pH to neutral after the reaction is completed, adding a free radical initiator and stirring for 20-60 minutes, wherein the crosslinking agent is selected from methyltriethoxysilane; S2: adding methacrylate or acrylate to the emulsion A obtained in step S1, mixing and emulsifying to obtain emulsion B; S3: adding a surface coating agent to the emulsion B, reacting for a period of time, and then adding a terminator to terminate the reaction, wherein the surface coating agent is KH570 or glycidyl methacrylate.
2. The epoxy resin composition according to claim 1, characterized in that The siloxane monomer is one, two or more of octamethylcyclotetrasiloxane, hexamethylcyclotrisiloxane and decamethylcyclopentasiloxane.
3. The epoxy resin composition according to claim 1, characterized in that The methacrylate monomer is selected from methyl methacrylate, ethyl methacrylate or propyl methacrylate, and the acrylate monomer is selected from methyl acrylate, ethyl acrylate or propyl acrylate.
4. The epoxy resin composition according to claim 1, characterized in that The epoxy resin is a mixture of bisphenol A epoxy resin and polyurethane modified epoxy resin, and the mass ratio of the bisphenol A epoxy resin to the polyurethane modified epoxy resin is 4-20:
1.
5. The epoxy resin composition according to claim 1, characterized in that The acid catalyst is selected from p-toluenesulfonic acid and dodecylbenzenesulfonic acid, the emulsifier is selected from OP-10, the surfactant is selected from sodium dodecyl sulfate, sodium oleoyloxyethanesulfonate, or sodium fatty alcohol polyoxyethylene ether sulfate, and the terminator is selected from p-methoxyphenol or hydroquinone.
6. The epoxy resin composition according to claim 1, characterized in that: The mass ratio of the siloxane monomer, the crosslinking agent, the acidic catalyst, the emulsifier, the surfactant, the methacrylate or acrylate, and the surface coating agent is 25-35:4-8:0.5-2:0.5-2:0.5-2:20-25:1-5, and the mass volume ratio of the siloxane monomer and water is 1g:(8-12)mL.
7. The epoxy resin composition according to claim 1, characterized in that The reaction temperature of step S1 is 60-100°C, and the reaction time is 2-5 hours; the reaction temperature of step S2 is 60-100°C, and the reaction time is 2-5 hours; the reaction temperature of step S3 is 60-100°C, and the reaction time is 0.5-2 hours.
8. The epoxy resin composition according to claim 1, characterized in that The modified core-shell rubber particles are obtained by demulsification and freeze drying.
9. A prepreg, characterized in that: The invention comprises the epoxy resin composition according to any one of claims 1 to 8 and glass fiber.
10. A fiber-reinforced composite material, characterized in that: The fiber-reinforced composite material is obtained by curing the prepreg according to claim 9.
11. The method for preparing a fiber-reinforced composite material according to claim 10, characterized in that: The method comprises: The prepreg according to claim 9 is cured at a temperature of 50-150° C. and a curing time of 4-10 hours.
12. Use of the epoxy resin composition according to any one of claims 1 to 8, or the prepreg according to claim 9, or the fiber-reinforced composite material according to claim 10 in a wind turbine blade, characterized in that: The epoxy resin composition, prepreg or fiber-reinforced composite material can improve the fracture toughness of wind turbine blades.
Citation Information
Patent Citations
Nanometer core-shell rubber particle toughening epoxy resin compound and preparation method of nanometer core-shell rubber particle toughening epoxy resin compound
CN105176003A
Toughening agent with core-shell structure as well as preparation method and application of toughening agent
CN116715816A